Photovoltaic and antimicrobial potentials of electrodeposited copper nanoparticle - Wang, L. (2019)
Nanoparticles have been paid a great attraction in interdisciplinary sciences owing to their unique characteristics. Different nanoparticles were synthesized in metallic and non-metallic states, showing varied sizes for down-stream applications. Copper nanoparticle (CuNP) has a special attention due to its great electrical, catalytic, optical and mechanical properties. In this research, CuNP was prepared by the electrolytic deposition and characterized its morphological and structural behaviours by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy. SEM displays the irregular agglomerated particles, whereas with TEM the sizes were determined as 40 Â± 10 nm. The peaks with XPS analysis were noticed at 932.1 for Cu(2p3/2), 944.1 eV and 952.1 eV for Cu(2p1/2). Whereas, the representative peaks for copper were placed at 43.7Â° 50.7Â° and 74.3Â° corresponding to (111), (200) and (220) under XRD observations. CuNP vibration peaks were monitored at 1635 cmâ1 with FTIR and a sharp peak at 617.6 cmâ1 is representing Cu-O group due to the occurrence of Cu2O. The antimicrobial activity of the electrodeposited CuNP was proved against the fungus, Aspergillus niger. Further, ITO/CuNP/CuI/Cu (Indium Tin Oxide/Copper Nanoparticle/Copper Iodide/Copper) substrate solid-state photovoltaic cell was fabricated by CuNP electrodeposition on the CuI substrate. It was anchored by IâV characteristics, apparent that a rapid current enhancement after deposition of the CuNP. Â© 2018 Elsevier B.V.